1989
DOI: 10.1007/bf02372591
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and behavioral effects of selected insecticides on theHeliothis parasitoidMicroplitis croceipes

Abstract: Toxic and behavior-modifying actions of several formulated insecticides were determined for Microplitis croceipes (Cresson), a braconid parasitoid of Heliothis spp. Exposure of adult parasitoids to cotton plants sprayed at recommended field rates with a pyrethroid/formamidine mixture (fenvalerate/chlordimeform) resulted in significantly higher mortality rates (10.4 to 22.6 percent) than in controls. Exposure to the carbamate thiodicarb resulted in similar rates of mortality. Only methomyl, a type of carbamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Studies, such as the present one, that also monitor altered foraging behavior of beneficial insects as a result of insecticide exposure, are rarely performed, even though this is a key behavior for beneficial insect effectiveness. Elzen et al (1989) showed a decrease in flight activity toward cotton plants by M. croceipes females sprayed directly with a fenvalerate/chlorodimeform mixture. Flight activity in this insect is usually considered to be an indicator of foraging efficiency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies, such as the present one, that also monitor altered foraging behavior of beneficial insects as a result of insecticide exposure, are rarely performed, even though this is a key behavior for beneficial insect effectiveness. Elzen et al (1989) showed a decrease in flight activity toward cotton plants by M. croceipes females sprayed directly with a fenvalerate/chlorodimeform mixture. Flight activity in this insect is usually considered to be an indicator of foraging efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…(3) Mortality frequently is the only effect that insecticides are screened for, while more conspicuous sublethal effects in beneficial insects, such as altered behavior, reduced reproduction, and reduced longevity, are largely overlooked (Elzen, 1990). Like mortality, sublethal effects can severely reduce the performance of the biological control agent (Jacobs et al, 1984;Elzen et al, 1989;Roger et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Certain pesticides (insecticides and fungicides) may also exhibit repellent activity [16,[41][42][43][44][45][46] or alter host plant physiology [13,47] thus indirectly affecting the ability of natural enemies to regulate existing arthropod pest populations [48].…”
Section: Indirect Effects Of Pesticides On Natural Enemiesmentioning
confidence: 99%
“…While evaluations associated with the direct effects of pesticides on natural enemies are important, what are actually more relevant are the indirect or delayed effects of pesticides because this provides information on the long-term stability and overall success of a biological control program when attempting to integrate the use of pesticides with natural enemies [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation